1998
DOI: 10.1159/000016436
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Clinical Studies on the Caries-Inhibiting Effect of Fluoride Gel treatment

Abstract: A meta-analysis was performed on published data on the caries-inhibiting effect of fluoride gel treatment in 6- to 15-year-old children. The purposes of this meta-analysis were: (1) to calculate the overall caries-inhibiting effect of clinical fluoride gel treatment studies, based on explicit selection criteria, and (2) to explore factors potentially modifying the effect of fluoride gel treatment in caries prevention, concerning the baseline caries prevalence of the target population, the general fluoride regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
3
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 18 publications
5
60
3
3
Order By: Relevance
“…In a metaanalysis of fluoride gel trials, van Rijkom et al included nine studies (ten comparisons) of professionally applied gels published between 1970 and 1992. 7 The overall average prevented fraction was 22% (95% CI = 18-25%) indicating good evidence of effectiveness in permanent teeth. All of the PATF studies used APF gel, application frequency varied from 1-2 times per year, and the ages of subjects ranged from 6-15 years.…”
Section: Caries Preventionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a metaanalysis of fluoride gel trials, van Rijkom et al included nine studies (ten comparisons) of professionally applied gels published between 1970 and 1992. 7 The overall average prevented fraction was 22% (95% CI = 18-25%) indicating good evidence of effectiveness in permanent teeth. All of the PATF studies used APF gel, application frequency varied from 1-2 times per year, and the ages of subjects ranged from 6-15 years.…”
Section: Caries Preventionmentioning
confidence: 90%
“…The number of children that must be treated to prevent one decayed surface is esti- preventing caries in the permanent dentition of children mated at 18 if caries incidence is low, but only 3 for groups with high caries incidence. 7 A possible indication for the use of PATF is adults with exposed root surfaces. The problem of root caries is likely to increase due to population aging and the increased retention of teeth.…”
Section: Which Patients Should Receive Patf?mentioning
confidence: 99%
“…1 This new trial was published after the completion of two relevant systematic reviews which are mentioned in the discussion section of the trial report. One was carried out by the same group of researchers who conducted this trial 2 and the other was a recent Cochrane review, which contains information from nearly 8000 children. 3 The results of the new trial have not been formally integrated into the 1998 van Rijkom et al review, 2 but because Cochrane reviews are usually updated every 2 years, they should be incorporated in the next version of the Cochrane review.…”
Section: Commentarymentioning
confidence: 99%
“…In an example from dentistry, discussed in Part 8 of this series, a review (Rijkom et al, 1997) of the usefulness of fluoride gel for the prevention of caries, showed that the overall effect of the gel is to reduce the incidence of caries by 22% per year. 20 Calculations showed that, if without the gel the incidence of caries were 0.25 DMFS per year, it would be necessary to treat 18 teeth with the gel for a year in order to save one DMFS. The NNT decreased to 9, 4.5 and 3 if the incidences without the gel were 0.50, 1.00 and 1.50 DMFS per year, respectively.…”
Section: The Number Needed To Treat (Nnt)mentioning
confidence: 99%